2020
DOI: 10.1177/0021998320911719
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of friction and shear strength enhancement on delamination prediction

Abstract: This study considers the intra-laminar damage mode in composite structures and its effect on delamination prediction. The progressive damage models for matrix cracking and fibre failure in ABAQUS, based on Hashin's model, are only available for shell elements. The results presented here show that the predicted matrix cracking based on the damage model presently available in ABAQUS diverges from experimental results. A new model based on strain failure criteria, which can be used with both shell elements and 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In this study we also introduce the effect of friction (as recommended by many researchers for composites [28][29][30][31][32][33] but as yet not used in FMLs), as it has been proven that including both friction and enhanced shear strength gives more accurate results for the simulation of the effect of through-thickness compression on mode-II shear failure. This has been achieved using a further modification to the cohesive zone model (F-S/CZM) coupling both friction and enhanced shear strength and implemented by combining equations ( 1) and ( 8)…”
Section: Modified Cohesive Zone Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we also introduce the effect of friction (as recommended by many researchers for composites [28][29][30][31][32][33] but as yet not used in FMLs), as it has been proven that including both friction and enhanced shear strength gives more accurate results for the simulation of the effect of through-thickness compression on mode-II shear failure. This has been achieved using a further modification to the cohesive zone model (F-S/CZM) coupling both friction and enhanced shear strength and implemented by combining equations ( 1) and ( 8)…”
Section: Modified Cohesive Zone Modelmentioning
confidence: 99%
“…Although many studies have been performed considering the bending behaviour of FML structures as described above, the effect of friction and enhanced shear strength caused by through-thickness compression has not been considered. Recent studies on composite structures ( [22][23][24][25][26][27][28][29][30][31][32][33]) however, have revealed that including through-thickness compression stresses in cohesive zone models for interlaminar damage behaviour results in significant improvements in simulation results when compared with experiments for structures subjected to similar loading effects such as biaxial loading, low velocity impact and bending loads. Hassan Ijaz et al [22], developed an inelastic damage model in order to simulate damage in Z-pinned laminated composite structures with friction effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 This criterion has been successfully utilized by many researchers e.g. Hameed et al., 26 Zou and Hameed, 27 Belnoue et al. 17 and Kawashita and Hallett, 12 and is written as; where τn,normal τs,normal τt are the normal, shear and tear stresses respectively and where the operator 〉〈|xnormal is defined as; …”
Section: Developed Fatigue Damage Degradationmentioning
confidence: 99%
“…25 This criterion has been successfully utilized by many researchers e.g. Hameed et al, 26 Zou and Hameed, 27 Belnoue et al 17 and Kawashita and Hallett, 12 and is written as;…”
Section: Developed Fatigue Damage Degradationmentioning
confidence: 99%